Legal Protection of Labour’s Freedom of Union Againts Union Busting in Indonesia - Al Uyun, Dhia; Buryahika, Edgar; Siagian, Daniel Alexander (Universitas Negeri Surabaya, 2024)
Freedom of association, assembly and expression is part of human rights that must be respected, fulfilled and protected. Constitutionally, freedom of association for workers/laborers has been guaranteed in Article 28E paragraph (3) which confirms that everyone has the right to freedom of association, assembly and opinion. Basically, trade unions / labor unions are organizations formed from, by, and for workers/workers both in the company and outside the company that are free, open, independent, democratic and responsible in order to fight, defend and protect the rights and interests of workers/workers and improve welfare. However, in practice there are various forms of violation of freedom of association for workers, one of which is the suppression of trade unions (Union Busting) which is often intended as an effort to weaken the bargaining position of workers against the company. Union Busting is a restrictive measure against the establishment and implementation of workers ' freedom of association, beginning with discrimination against workers. Union busting actions carried out by employers against unions, are usually carried out through unilateral layoffs, demositions, and mutage of positions. The restriction of freedom of association is contradictory as Article 104 Paragraph (1) of Law No. 13 of 2003 concerning manpower confirms that every worker/worker has the right to form and become a member of a trade union/trade union. Legal protection is the protection of human dignity and recognition of human rights owned by legal subjects based on legal provisions and as a collection of laws or rules that will be able to protect one thing from another. Legal protection is an effort to prevent and overcome the violation or non-fulfillment of the rights of legal subjects. Legal protection against Union Busting is actually needed to protect workers ' rights in forming and running unions so that there is a healthy working relationship between workers and companies.